Values and guidelines regarding the preservation of the health of the population in the surveillance zone of NPP during martial law (Environment & Health, 2025)
The aim: to study the value orientations and guidelines of the population of the surveillance zone of NPP and to determine their significance in the problem of health preservation during martial law.Materials and methods. The place of health in the individual hierarchy of terminal and instrumental values; social guidelines regarding its preservation. Factors affecting health; viability and degree of responsibility for one’s life. The survey was conducted among the adult population of the surveillance zone of the Southern-Ukrainian NPP of the Voznesensk district of the Mykolaiv region. Sociological, socio-psychological, analytical, mathematical research methods are applied.Results. Guidelines for maintaining health are in full compliance with the chosen component integrity of values-goals and values-means. In the І group of respondents, where health is the most important thing in life, the main terminal and instrumental value is health. In the І group, there is uncertainty regarding control over one’s life, which during the war has a negative effect on the general vitality of a person both in the mental and physical dimensions. In the II group, where the main social guideline is the well-being of the family, the main terminal value is a happy family life, and the tools of achievement are health and material wealth. In the III and IV groups, where health is equal to all other spheres of life and is declared as a life without limitations, a person chooses independence and freedom as the main value, and perseverance and hard work as a tool.Conclusions. For the rural population, the value of health is at the same time the main goal in life and a tool for achieving one’s life's goal. For the urban population, the main goal in life is independence, freedom, and as a means - perseverance and hard work. Choice of health value correlates with factors of health concern. The choice of independence and freedom as the goal of one’s existence during the war directly affects the formation of vitality and is a combination of a change of consciousness and concentration of life resources. With the beginning of the war, a restructuring of the hierarchy of terminal values took place - the value of independence and freedom moved from 5-th place before the war to 2-nd place.
Keywords: health; values; social guidelines; nuclear power plant surveillance zone; martial law